1996
DOI: 10.1212/wnl.46.5.1226
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of migraine and idiopathic intracranial hypertension without papilledema

Abstract: Eighty-five patients with refractory transformed migraine type of chronic daily headache (CDH) had spinal tap as a part of diagnostic work-up. Twelve had increased intracranial pressure without papilledema, transient visual obscurations, or visual field defects. The headache profile of these 12 patients was not different from that of transformed migraine type of CDH. Acute headache exacerbations responded to specific antimigraine agents such as ergotamine, dihydroergotamine (DHE), and sumatriptan, whereas prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
129
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(136 citation statements)
references
References 13 publications
4
129
1
2
Order By: Relevance
“…In study by Kathleen et al, that assessed the clinical characteristics of IIH patients with and without papilledema, shows that the prevalence of migraine headache in patients with- out papilledema was 65% and in patients with papilledema was 45%. 10 Curiously there is relation between migraine and intracranial hypertension that is very complex and need more study. Mathew et al assessed the prevalence of intracranial pressure in patients with chronic unresponsive migraine headache, in this study 44 patients with chronic migraine headache and stenosis in sinus vein in mri venography were assessed that 86.4% of this patients have raised intracranial hypertension (csf pressure >200 mmH2O).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In study by Kathleen et al, that assessed the clinical characteristics of IIH patients with and without papilledema, shows that the prevalence of migraine headache in patients with- out papilledema was 65% and in patients with papilledema was 45%. 10 Curiously there is relation between migraine and intracranial hypertension that is very complex and need more study. Mathew et al assessed the prevalence of intracranial pressure in patients with chronic unresponsive migraine headache, in this study 44 patients with chronic migraine headache and stenosis in sinus vein in mri venography were assessed that 86.4% of this patients have raised intracranial hypertension (csf pressure >200 mmH2O).…”
Section: Discussionmentioning
confidence: 99%
“…The 77% of this patient, experience decreased headache with treatment of ICP raising. 10 In another study by Ramadan that assessed the IIH in the patients with chronic daily headache, 12 patients have intracranial hypertension that do not have any evidence of papilledema, visual obscuration and decreased visual acuity and the treatment with acetazolamide reduce their chronic headache. 11 However, it seems that in any patients with chronic migraine headache that is refractory and do not respond to usual prophylactic migraine headache, it is essential that done spinal tap for rule out of idiopathic intracranial hypertension without papilledema.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Papilloedema is present in the majority of patients with IIH and usually occurs bilaterally [11], although unilateral occurrences were reported in 10% of cases [12,13]. Recent evidence revealed that papilloedema is caused interruptions in the optic nerve (ON) metabolism as a result of the high intracranial pressure transmitted to the subarachnoid space surrounded the ON, leading to edema, ischemia, and eventual visual impairment or loss.14 Choroidal folds arise from globe compression from the distended optic nerve sheath leading to globe distortion and acquired hyperopic shift [15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…It is recognised that intractable chronic migraine can be triggered by persistently raised intracranial pressure. 15 These patients typically give a history of generalised headache that is present on waking, and gets better as the day goes on. It is generally worse with recumbency.…”
mentioning
confidence: 99%